2012
DOI: 10.1111/ctr.12031
|View full text |Cite
|
Sign up to set email alerts
|

Living vs. deceased donor liver transplantation for hepatocellular carcinoma: a systematic review and meta‐analysis

Abstract: Experimental studies suggest that the regenerating liver provides a "fertile field" for the growth of hepatocellular carcinoma (HCC). However, clinical studies report conflicting results comparing living donor liver transplantation (LDLT) and deceased donor liver transplantation (DDLT) for HCC. Thus, disease-free survival (DFS) and overall survival (OS) were compared after LDLT and DDLT for HCC in a systematic review and meta-analysis. Twelve studies satisfied eligibility criteria for DFS, including 633 LDLT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 33 publications
1
77
0
Order By: Relevance
“…There is no convincing evidence that graft type has a significant influence on recurrence rates. Two recent meta-analysis comparing HCC recurrence rates between living donor liver transplant and deceased donor liver transplant came to opposite conclusions (12,13). Additionally, there is no evidence that a donor after cardiac death (DCD) compared to donor after brainstem death (DBD) liver has any influence on HCC recurrence rates post-transplant (14,15).…”
Section: Review Articlementioning
confidence: 99%
“…There is no convincing evidence that graft type has a significant influence on recurrence rates. Two recent meta-analysis comparing HCC recurrence rates between living donor liver transplant and deceased donor liver transplant came to opposite conclusions (12,13). Additionally, there is no evidence that a donor after cardiac death (DCD) compared to donor after brainstem death (DBD) liver has any influence on HCC recurrence rates post-transplant (14,15).…”
Section: Review Articlementioning
confidence: 99%
“…No prospective study has ever challenged the matter, however, there were two systematic reviews with meta-analyses so far. Grant et al (24) performed a meta-analysis on 12 retrospective studies comparing the recurrence rates and recurrence-free survival between LDLT and DDLT recipients. A total of 633 LDLTs and 1,232 DDLTs were enrolled, and the study provided evidence of lower disease-free survival after LDLT compared with DDLT for HCC [hazard ratio =1.59; confidence interval (CI): 1.02−2.49; P=0.041].…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…These found overall survival rates to be similar between the two groups. One of these, by Grant et al [66] found LDLTs to be associated with decreased disease-free survival rates. On the other hand, Liang et al [67] performed a subgroup analysis of patients within the Milan criteria and found similar survival outcomes between the two groups.…”
Section: Living Donor Liver Transplantationmentioning
confidence: 99%